A Qualitative Analysis Of Implementing Online Workshops For Automotive Maintenance In DKI Jakarta - Taufan Herjanto (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This research aims to explore the implementation of online workshops for automotive maintenance in DKI Jakarta. The study adopts a qualitative approach to gain insights into the effectiveness and challenges of conducting such workshops. Purposive sampling is employed to select participants with diverse backgrounds and experiences in automotive maintenance. Data collection methods include interviews, observations, and document analysis. Thematic analysis is utilized to identify patterns, themes, and key findings from the collected data. The study reveals valuable insights into the feasibility, benefits, and limitations of implementing online workshops for automotive maintenance in DKI Jakarta. The findings contribute to a deeper understanding of the potential of online platforms in facilitating vocational education and skill development in the automotive sector